Sodelovanje med zdravniki družinske medicine in specialisti psihiatri pri zdravljenju bolnikov z depresijo - Rotar-Pavlič, Danica (Zdravniški vestnik, 2011)
Background: By 2015, mental illness will become the greatest healthcare burdenin the world. Within the community, people with depression are most often treated by family doctors. Treatment for depression also includes psychiatric specialists, with varying cooperation between the primary care provider and the psychiatrist. This studyćs goal was to define cooperation between family doctors and psychiatric specialists when treating patients withdepression. Methods: In 2009 six focus groups were held that included general practitioners. The data were analyzed using qualitative methods. Results: Seventeen topics and related categories were developed for the study.One of these related to the cooperation between primary care providers and psychiatric specialists. Family doctors see psychiatrists as responsible for working with more challenging patients and as intermediaries in evaluatingsick leave and assessing ability to work. Psychiatrists offer familydoctors support in the education process and in terms of supervision. Numerous factors influence referral from primary to secondary level, includingpatientsć and doctorsć personal characteristics. Conclusions: Achieving the goals of treating patients with depression requires not only expertise, organization at the primary care level, and a method of communication between patients and doctors, but also cooperation between primary care providers and psychiatric specialists. This ought to take place in compliance with professional criteria and not as a result of the patientćs condition and pressure from the patient. Representatives of both specializations should establish ways to work together and clarify the issue of information exchange and (in)appropriate referrals for obtaining opinions regarding sick leave and disability-based retirement.
Keywords: depresija; družinska medicina; therapy; zdravljenje